A phase I/II study of ixazomib, pomalidomide, and dexamethasone for lenalidomide and proteasome inhibitor refractory multiple myeloma (Alliance A061202). Issue 12 (6th October 2021) - Voorhees, Peter M.; Suman, Vera J.; Tuchman, Sascha A.; Laubach, Jacob P.; Hassoun, Hani; Efebera, Yvonne A.; Mulkey, Flora; Bova‐Solem, Misty; Santo, Katelyn; Carlisle, Destin; McCarthy, Philip L.; Richardson, Paul G.
Abstract: Preclinical studies have demonstrated activity of the oral proteasome inhibitor (PI) ixazomib (IXA) in bortezomib‐resistant multiple myeloma (MM) and synergy with immunomodulatory drugs. We therefore conducted a phase I/II study to establish the safety and preliminary efficacy of IXA with pomalidomide (POM) and dexamethasone (DEX) in lenalidomide (LEN)/PI‐refractory MM. Dose escalation established a 4 mg dose of POM and IXA and 20/40 mg dose of DEX as the maximum tolerated dose. The phase II portion of the trial was redesigned and started anew after six patients had been randomized to IXA‐POM‐DEX due to a rapidly changing treatment landscape. Among the 29 evaluable LEN/PI‐refractory patients treated with IXA‐POM‐DEX in phase I/II, the overall response rate (partial response or better) was 51.7% with a median duration of response of 16.8 months (range 56 days to 4.1 years), median progression‐free survival of 4.4 months (95% confidence interval [CI]: 3.0–18.4), and median overall survival of 34.3 months (95% CI: 19.2 to not reached). Hematologic, gastrointestinal, and constitutional adverse events were common and consistent with the side‐effect profiles of the individual agents. Our results support further evaluation of this all‐oral regimen in relapsed/refractory MM.